2013
DOI: 10.1080/09640568.2012.724667
|View full text |Cite
|
Sign up to set email alerts
|

Economic valuation of the non-use attributes of a south-western coastal wetland in Bangladesh

Abstract: Being located in the south-western hydrological region of Bangladesh, Chanda Beel, a coastal freshwater wetland, is threatened by over-exploitation of resources. Therefore, this study made an attempt to estimate the non-use values of the wetland to realise its hidden values. The study used the contingent valuation method (CVM) method to place a value on the non-use attributes of the wetland and the results show that the non-use value is approximately US$ 0.48 million annually. The effects of socio-economic fac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
1
2

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 23 publications
1
8
1
2
Order By: Relevance
“…The marginal effect shows that an increase of 10,000 RMB (1 RMB ≈ 0.17 USD) in net household income decreases participation probability by three percentage points. This result differs from the positive impact reported by Ghosh and Mondal [17] and Petrolia and Kim [23]. This finding may be attributed to the fact that farmers with higher net household incomes tend to be non-cropping households and their main income sources are non-agricultural activities (the correlation between household net income and non-agricultural income is about 0.97).…”
Section: Resultscontrasting
confidence: 56%
See 3 more Smart Citations
“…The marginal effect shows that an increase of 10,000 RMB (1 RMB ≈ 0.17 USD) in net household income decreases participation probability by three percentage points. This result differs from the positive impact reported by Ghosh and Mondal [17] and Petrolia and Kim [23]. This finding may be attributed to the fact that farmers with higher net household incomes tend to be non-cropping households and their main income sources are non-agricultural activities (the correlation between household net income and non-agricultural income is about 0.97).…”
Section: Resultscontrasting
confidence: 56%
“…Our results also suggest that age has no significant influence on farmers' willingness to participate in wetland restoration in our sample. Similar to Ghosh and Mondal [17] and Zhang et al [20], gender is also found to not affect farmers' willingness to participate. Consistent with most empirical results, education level (Education) plays an important role in farmers' participation decisions.…”
Section: Resultssupporting
confidence: 51%
See 2 more Smart Citations
“…The positive relationship between these variables is generally supported by the literature. For example [16,50,[52][53][54][55] indicated that highly educated people and those with higher income are more supportive of nature preservation and have higher WTP.…”
Section: Discussion Of the Resultsmentioning
confidence: 99%